SOME PROBLEMS IN MAINTAINING SUSTAINABILITY OF INDONESIA'S FORESTS: DESCRIPTIVE STUDY - Handoko, Cecep (Association of Indonesian Forestry and Environment Researchers and Technicians, 2014)
Indonesia's forests have economic, social, and environmental benefits. Some national efforts, as well as support from the global community for sustaining forest development in Indonesia have been done. However, some problems were still reported during the implementation of the forest development. Thorough analysis was needed to formulate the root of the problems, and to identify solutions/supports to the current forest development to achieve its sustainability. Descriptive analysis was used in this study. The results indicated that sustainable forest development in Indonesia was still faced with the problems of uncertainty of management, insufficient management capacity, and lack of law enforcement. These conditions were indicated by high conflict of interests as well as lack of support from stakeholders, not enough forest management actions at site-level, and high forest degradation. Aiming at overcoming problems of sustainable forest development and maintaining sustainability of Indonesia's forest, national forest management needs to embrace more space for communication, openness, mutual learning, collaboration in addressing forest conflicts, and determining the future direction of its sustainability goal of management.